Optimizing the Protection of Children and Women Towards a Great Indonesia - Ichsan, Nursyamsi; Fatmawaty Syam, Andi; Hasmiati Attas, Nasrah; Nasir, Citra; Nirwan (Cendekiawan Indonesia Timur, 2022)
This study examines a legal counseling activity aimed at enhancing the protection of children and women in Parara Village, North Luwu Regency, as part of a broader vision for a safer and more empowered Indonesia. Conducted by Law Study Lecturers from Mega Buana Palopo University in June 2023, this community service initiative was designed to raise awareness and educate local residents on the legal rights and protections available for vulnerable populations. Through a series of meticulously planned educational segments and interactive discussions, the program sought to equip participants with the knowledge and tools necessary to combat and prevent instances of violence within their community. The preparation phase involved collaborative efforts with village officials and law students, ensuring a comprehensive approach to logistical and content-related aspects of the event. The implementation highlighted the community's engagement and interest, featuring contributions from various stakeholders including the Village Head and the legal academic community. This paper discusses the significance of such educational outreach efforts in fostering a culture of legal literacy and advocacy, contributing to the broader goal of societal well-being and safety.